Implementation Issues in Functional Family Therapy: A Narrative Analysis of the Evidence. (May 2020) - Weisman, Clio; Montgomery, Paul
This analysis of functional family therapy (FFT) studies examines whether their variable outcomes are attributable to implementation issues. Studies were identified firstly, by way of a recent overview, supplemented by an update of a highly sensitive search including 15 databases, 10 websites, all existing relevant reviews, gray literature as well as contacting experts in the field. Updated searches were conducted in August 2018 and were analyzed according to the Oxford Implementation Index and an assessment of supervision quality. In total, the search yielded 150 records; 48 full texts were retrieved of which 32 were excluded leaving 16 studies containing 5, 320 unique participants included for analysis. There was no evidence of reported harm. Improved training and supervision were associated with better core outcomes. Although there was no apparent dose relationship, it appears that implementation issues are important and also that class and ethnicity were identified for areas of further study.